1998
DOI: 10.1159/000022053
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Body Composition in Elderly: Accuracy of Bioelectrical Impedance Analysis

Abstract: Background: In the literature there are several body impedance analysis (BIA) prediction equations generally determined in younger populations and their accuracy in the elderly has not been adequately confirmed. Objective: We verified the reliability of the BIA method in a body composition study in the elderly. Methods: To assess the accuracy of bioelectrical impedance analysis we compared this method with dual photon absorptiometry (DPA), assumed as a gold standard; body composition was predicted by seven BIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 25 publications
1
29
1
Order By: Relevance
“…33 The variability in fat-free mass hydration in the elderly has been reported to be larger than in younger individuals, which may decrease the accuracy of the BIA method for this demographic. 34 In this study, however, we observed a high level of agreement between BIA-measured ECW and that calculated using the Moore et al equations, despite using older individuals as control subjects. Further validation studies are needed to evaluate the clinical usefulness of the present method for quantifying the degree of fluid accumulation in a wide range of ADHF patients.…”
Section: -24contrasting
confidence: 68%
“…33 The variability in fat-free mass hydration in the elderly has been reported to be larger than in younger individuals, which may decrease the accuracy of the BIA method for this demographic. 34 In this study, however, we observed a high level of agreement between BIA-measured ECW and that calculated using the Moore et al equations, despite using older individuals as control subjects. Further validation studies are needed to evaluate the clinical usefulness of the present method for quantifying the degree of fluid accumulation in a wide range of ADHF patients.…”
Section: -24contrasting
confidence: 68%
“…some differences were observed in the associations of risk factors with MAMc and FFMi. this could be explained by the greater inaccuracy of BiA in assessment of FFMi in older people, predominantly due to fat-free mass hydration variability (41,42). non-participation bias is possible, as men too unwell to attend the physical examination would have been excluded, potentially eliminating men with extremely low muscle mass and underestimating observed associations.…”
Section: Low Muscle Mass In Older Men: the Role Of Lifestyle Diet Anmentioning
confidence: 99%
“…To our knowledge, only three BIA formulas for the elderly have been published to date: by Deurenberg et al [14], Baumgartner et al [15] and Roubenoff et al [16], in selected populations of the Netherlands, New York, USA and Massachusetts, USA, respectively. These formulas may not be valid in the elderly Swiss population, since BIA formulas are often population-specific [17]. On the other hand, Kyle et al [18] developed a BIA formula specific for the Swiss population, for all ages, but only 42 men and 48 women over 70 years were included.…”
Section: Introductionmentioning
confidence: 99%